Transformative Christian Education to Fight Against Human Trafficking - Kapu Enda, Andriarto (Didache: Journal of Christian Education, 2024)
This writing is driven by the increasing cases of human trafficking in Sumba, a serious crime against humanity and a violation of human rights. Many men and women working abroad, along with numerous women and children, have fallen victim to trafficking, where they are exploited without fair wages or forced into sexual labor. In recent years, many victims of trafficking have returned home with missing organs, or worse, have lost their lives. The author believes that the church must take action by raising awareness and resistance through transformative Christian education. Thus, this writing aims to analyze how transformative Christian education can play a role in combating human trafficking. The research is based on a qualitative methodology, using data collection methods such as literature review, observation, and interviews. The findings indicate that Christian education within the church has yet to address human trafficking, as it currently focuses solely on worship services. The author suggests that Christian education in congregations should be re-evaluated to include topics related to human trafficking. The Christian educational content should not only be drawn from the Bible but also from real-world experiences and social issues like human trafficking that affect the community. The goal of Christian education should be to inspire transformation and change within the congregation